2021
DOI: 10.1021/acs.orglett.1c00720
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Total Synthesis of Siladenoserinols A and D

Abstract: The stereoselective total synthesis of siladenoserinols A and D has been accomplished using carbohydrate as a chiral template. The feature of this work is to build the medicinally privileged 6,8-DOBCO scaffold through a cascade reaction of hydrogenation/deacetalization/ketalization in a one-pot process, that is, to take advantage of a thermodynamically controlled bicyclization of polyhydroxyketone under HCl/MeOH reaction conditions. The current cost-effective synthetic strategy could facilitate the bioactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…The endgame of the synthesis was based on a Horner–Wadsworth–Emmons olefination step between 1 91 and aldehyde 192 , ketal deprotection, and sulfamate installation. Alternative syntheses of siladenoserinols A ( 120 ), D ( 123 ) and H ( 127 ), 217 and phosphatidylcholine esters PEIPC and PECPC, 270 have appeared recently where commercially available α-GPC and 1-palmitoyl-lysophosphatidylcholine (16 : 0 Lyso-PC) were used as the phosphate source, respectively.…”
Section: Synthetic Approaches To Phosphate Estersmentioning
confidence: 99%
“…The endgame of the synthesis was based on a Horner–Wadsworth–Emmons olefination step between 1 91 and aldehyde 192 , ketal deprotection, and sulfamate installation. Alternative syntheses of siladenoserinols A ( 120 ), D ( 123 ) and H ( 127 ), 217 and phosphatidylcholine esters PEIPC and PECPC, 270 have appeared recently where commercially available α-GPC and 1-palmitoyl-lysophosphatidylcholine (16 : 0 Lyso-PC) were used as the phosphate source, respectively.…”
Section: Synthetic Approaches To Phosphate Estersmentioning
confidence: 99%
“…Afterward, Zhao and coworker's developed a synthetic method for the diastereoselective iminoacylation and amidoacylation of trisubstituted alkenes under covalent‐based NHC radical catalysis [8e] . Very recently, Du group explored a facile and efficacious strategy for synthesizing structurally diverse α‐sulfonyl ketones by a NHC‐catalyzed radical–radical coupling process [8i] . Inspired by these elegant works, we envisioned that if a work promoted by NHC via radical cascade cyclization to construct 2‐pyrrolidone, this reaction would be more attractive.…”
Section: Methodsmentioning
confidence: 99%
“…Syntheses of ascidian metabolites 19-bromoisoeudistomin U, 672 ritterazine B, 673 (−)-rossinone A, 674 (−)-herdmanine D 675 and siladenoserinol D 676 have been reported. Examination of the cellular effects of synthetic biselide A using image-based phenotypic screening identified that the macrolide can be added to the growing list of MNPs that target microtubules and microtubule dependent structures.…”
Section: Tunicates (Ascidians)mentioning
confidence: 99%